A Miniaturized Planar Monopole Antenna Based on a Coupling Structure for Compact Mobile Internet of Things (IoT) and Electric Vehicles (EVs) Device Applications in 5G, LTE, WLAN, WiMAX, Sirius/XM Radio, V2X, and DSRC Wireless Systems - Ming-An Chung; Chih-Wei Yang (International Journal of Antennas and Propagation)
A miniaturized internal antenna with monopole structure is constituted, including three radiating strips of a compact prototype and a back-coupling pad to improve the impedance matching, which achieves a wide bandwidth of 2.972 GHz between the operating frequencies of 2315–5285 MHz, and is introduced and researched. There is an urgent need for a complete frequency-continuous and large bandwidth design in the current wireless communication design to achieve a multimode, multifrequency, physical phenomenon design with large bandwidth and continuous operating frequency. The recommended antenna provides a broadband operation in an electric vehicles (EVs) and Internet of Things (IoT) devices application embedded in the wireless communication standard for 5G, LTE, V2X, WLAN, WiMAX, Sirius/XM Radio, V2X, and DSRC to support the multiband application. This design is embedded side edge of overall placement in the device and is integrated applicable to the trend of heterogeneous wireless multiple access networks in electric vehicle and Internet of Things system devices, which covered the 5G with supporting the band of n7/n38/n40/n53/n77/n78/n79/n90, the 4G with supporting the band of 7/38/40/41/42/43/48/67, the V2X and DSRC for the operating frequencies between 2500 and 5000 MHz, the Sirius/XM Radio for the operating frequencies of 2320–2345 MHz, the ISM band of WiFi and BT covering the band of 2450–2483.5 and 5150–5350 MHz, and the WiMAX also supporting the band of 2300–2690 and 3400–3690 MHz. Moreover, the compact antenna manufactured an FR4 material with the antenna area of 5 × 10 × 0.8 mm3 and the ground area of 33.5 × 10 × 0.8 mm3. The proposed design better benefits a narrow space on the PCB with a low profile and is easy to make with a circuit board design.